Foundations of Information and Knowledge Systems 9th International Symposium, FoIKS 2016, Linz, Austria, March 7-11, 2016. Proceedings - Gyssens, Marc.; Simari, Guillermo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the proceedings of the 9th International Symposium on Foundations of Information and Knowledge Systems, FoIKS 2016, held in Linz, Austria, in March 2016. The 14 revised full papers presented papers were carefully reviewed and selected from 23 submissions. The papers address various topics such as reasoning about beliefs, uncertainty, incompleteness, and inconsistency, inference and problem solving, querying and pattern mining, dealing with knowledge, logics and complexity.
Reasoning about Beliefs, Uncertainty, Incompleteness, and Inconsistency -- Inference and Problem Solving -- Querying and Pattern Mining -- Dealing with Knowledge -- Logics and Complexity.
Keywords: Computer science; Mathematical logic; Mathematical statistics; Database management; Data mining; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management; Probability and Statistics in Computer Science; Artificial Intelligence (incl. Robotics).; Electronic books